Scabies outbreaks during 2019 in Al- Daseem, Al-Rusafa-Baghdad: A retrospective study - Abdul Razzaq, Bashar A.; Hassan, Tuka Y. (Journal of the Faculty of Medicine Baghdad, 2021)
AbstractBackground: Scabies is a skin infestation by the Sarcoptes scabiei mite. Scabies is transmitted through close personal contact. Settings like hospitals, prisons and childcare centers are at greater risk of outbreaks. Both male and female may be infected with scabies in any age groups. It is common in tropical climate countries poor people who live in rural areas and among displaced patients. It rises significantly among low economic status because skin diseases are significantly associated with a higher crowding index.Objectives: To estimate the prevalence of scabies in Al- Daseem region and identify factors associated with an increased risk of scabies among patients. Methodology: A retrospective cross sectional study was carried out about scabies outbreak in Al- Daseem area which located at Al-Rusafa side in Baghdad during 2019. Basic data were obtained from records of communicable disease section/public health director / Al-Rusafa health directorate. All registered cases during 2019 were included in the study, and then data computerized and analyzed using SPSS version 23 using frequency tables for the selected variables under study. Participants represented by students of Ali Al Wardi School (the only school in Al Daseem area) and from people live in this area (20% of them selected randomly). Data included socio-demographic information (age, sex, family member, and treatment). The diagnosis of scabies was based on their typical history of (itching that worsens at night, the distribution of lesions, and a history of contact with other family member infected with scabies). Results: A total of 11363 participants information were obtained from database, 6473were male and 4873 were female. There were 746 (6.6% of total) participants infected with scabies of them, there were 457 (7%) male patients and 289 (5.9%) female patients. There was significant association between scabies and gender of patients, P=0.018.According to the age groups of patients, there were 161 (6.4%) patients 6 years old, 337 (8.8%) patients within (7-12 years) age group, 82         (6.7%) patients within (13-19 years) age group, and there were 166 (4.3%) patients 20 years old. There was a significant difference between scabies and age group, p